Penerapan Pembelajaran Tematik Di Kelas 2 SDN 1 Semaya Kecamatan Sikur Tahun Ajaran 2020/2021 - Ranita Haeroni; A Hari Witono; Heri Setiawan; Khairun Nisa (Journal of Science Instruction and Technology, 2021)
This study aims to find out and describe how teachers apply thematic learning starting from planning, implementing, and assessing learning outcomes in grade 2 SDN 1 Semaya, Sikur District. This research was conducted in grade 2 SDN 1 Semaya, Sikur District. This type of research uses descriptive qualitative research with the research subject of teachers and students of grade 2 SDN 1 Semaya, Sikur District. Data collection techniques are interview guidelines, observation guidelines, and documentation. The data analysis technique used is the interactive model of Miles and Huberman, namely through data reduction (data reduction), data display (data presentation), and verification/conclusion (verification/drawing conclusions). The results showed that in the thematic learning planning in SDN 1 Semaya has not been implemented as it should. This is because respondents have not compiled a web of themes but respondents have set subjects to be combined, studied basic competencies and indicators of the content of subjects to be combined, chosen and established unifying themes/topics, compiling thematic learning syllabus, and prepared a learning implementation plan (RPP). The implementation of thematic learning in SDN 1 Semaya has not been carried out as it should because in the initial learning activities respondents have not carried out the activities of perception, motivation, and delivery of scenarios (steps). The core activities of learning are still fragmented and have not led to the theme used in learning. The methods used during the learning process are less varied. In addition, it also has not used innovative media in learning. The learning material still stands alone and does not lead to a theme. Learning is also not fully focused on learners. In closing activities respondents have not done reflection, conclude, feedback, and follow-up. The types of assessments that respondents use are tests and non-tests. Test assessment in the form of stuffing questions and non-test assessments in the form of attitude and portfolio observation assessments.